Diagrama de fases e ponto crítico quântico no CeCoIn5-xSnx: efeitos de pressão e concentração - Silva, Scheilla Maria Ramos da (2007)
The family of CeTIn5 materials (T=Rh,Ir,Co) has become a subject of intense research once they exibit several interesting phenomena such as pressure-induced superconductivity, coexistence of antiferromagnetism and superconductivity and Non-Fermi Liquid behaviour (NFL). In particular, CeCoIn5 is the heavy fermion (HF) superconductor which has the highest critical temperature (Tc) of this class of materials at ambient pressure, Tc = 2,3 K. Besides, the NFL behaviour observed in this compound also situates it near quantum criticality in P = 0. By setting a parallel with the antiferromagnetic CeRhIn5 compound, we could afirm that its pressure-temperature phase diagram is shifted to positive pressures relative to the first. The volume of the CeRhIn5 unit cell is approximately 1.7% larger than the CeCoIn5, which would explain that difference. Therefore, one hopes that a slight expansion of the CeCoIn5 unit cell is able to lead it to a magnetic-ordered phase and bring new insights concerning to the quantum criticality of this compound. The goal of expanding the cell lead to the substitution of In by Sn, once this process has generated an increase of the CeIn3 volume. However, no appreciable change in the CeCoIn5¡xSnx volume was detected. In this work, we investigate the effects caused by Sn doping in x £ T and P £ T phase diagrams, built from AC electrical resistivity measurements in monocrystalline samples of the CeCoIn5. Our results show that the Sn doping has generated a positive chemical pressure on the system due to the enhancement of hybridization, not allowing the observation of an ordered phase. Besides quenching the magnetic phase, Sn also rapidly suppresses the superconductivity by introducing disorder on the compound. Applying hydrostatic pressure, the critical temperature also decreases, being well described by a two-band-model for the superconductivity. This description shows that the critical pressure, where the superconductivity is suppressed, is linearly reduced with the Sn concentration. We also verified in the obtained phase diagrams the existence of two superconducting quantum critical points (QCP) adjusted by disorder and hybridization. A wide NFL regime is observed when concentration or pressure control parameter is varied. Above the superconducting region, a sublinear dependence as T2=3 for the resistivity was observed. This exponent is an indirect evidence of the ordered phase and it was only detected when the superconducting state is weakened by doping. The liquid Fermi behaviour is found beyond the QCP in both diagrams.